Design and Analysis of a Low Cost Wave Generator Based on Direct Digital Synthesis - Jian Qi; Qun Sun; Xiaoliang Wu; Chong Wang; Linlin Chen (Journal of Electrical and Computer Engineering, 2015)
Signal generators are widely used in experimental courses of universities. However, most of the commercial tests signal generators are expensive and bulky. In addition, a majority of them are in a fixed working mode with many little-used signals. In order to improve this situation, a small sized and highly accurate economic signal generator based on DDS technology has been developed, which is capable of providing wave signals commonly used in experiments. Firstly, it is introduced the basic principles of DDS and is determined the overall scheme of the signal generator. Then, it proposes a design of the hardware, which include power supply module, display module, keyboard module, waveform generating module based on DDS chip, and the minimum system module based on C8051F010. The signal generator was designed to output sine and square waveforms, and the other achieved performances included the frequency range 0.1 Hz–12.5 MHz, the frequency resolution 0.05 Hz–0.1 Hz, the output amplitude 1.0–4.5 V, the frequency accuracy Kfmin=94.12% and Kfmax=99.99%, and the signal distortion RTHDmin=0.638% and RTHDmax=11.67%.